Diagnostic and prognostic value of biomarkers in acute myocardial infarction. Issue 1122 (4th April 2019) - Chen, Yuqi; Tao, Yifei; Zhang, Lan; Xu, Weiting; Zhou, Xiang
Abstract: The incidence of acute myocardial infarction (AMI) has been increasing rapidly in recent years, seriously endangering human health. Cardiac biomarkers play critical roles in the diagnosis and prognosis of AMI. Troponin is a highly sensitive and specific biomarker for AMI diagnosis and can independently predict adverse cardiac events. Other biomarkers such as N-terminal B-type natriuretic peptide and C reactive protein are also valuable predictors of cardiovascular prognosis. Recently, several novel biomarkers have been identified for the diagnosis and risk assessment in patients with AMI. A multibiomarker approach can potentially enhance the diagnostic accuracy and provide more information for the early risk stratification of AMI. In this review, we will summarise the biomarkers discovered in recent years and focus on their diagnostic and prognostic value for patients with AMI.